Volume 2: Diagnostics and Detection; Drilling; Dynamics and Control of Wind Energy Systems; Energy Harvesting; Estimation and I 2015
DOI: 10.1115/dscc2015-9850
|View full text |Cite
|
Sign up to set email alerts
|

Trust-Based Optimal Subtask Allocation and Model Predictive Control for Human-Robot Collaborative Assembly in Manufacturing

Abstract: We develop a one human-one robot hybrid cell for collaborative assembly in manufacturing. The selected task is to assemble a few LEGO parts into a final assembled product following specified instructions and sequence in collaboration between the human and the robot. We develop a two-level feedforward optimization strategy that determines the optimal subtask allocation between the human and the robot for the selected assembly before the assembly starts. We derive dynamics models for human’s trust in the robot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Similar optimization approaches were used for other applications such as optimizing subtask allocation between human worker and collaborative robot in human–robot collaborative assembly in manufacturing. 35 In addition, a plethora of well-established classical optimization techniques are available in the state-of-the-art literatures. 34 However, many of these standard methods may not provide the most appropriate solution for the situation of HRI due to their complexity and lack of practicality, which motivated us to use the proposed search-based local optimization method.…”
Section: Evaluation Results For the Fac For Lightweight Objectmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar optimization approaches were used for other applications such as optimizing subtask allocation between human worker and collaborative robot in human–robot collaborative assembly in manufacturing. 35 In addition, a plethora of well-established classical optimization techniques are available in the state-of-the-art literatures. 34 However, many of these standard methods may not provide the most appropriate solution for the situation of HRI due to their complexity and lack of practicality, which motivated us to use the proposed search-based local optimization method.…”
Section: Evaluation Results For the Fac For Lightweight Objectmentioning
confidence: 99%
“…We formulated an MPC taking theoretical and conceptual inspiration from Rawlings and Mayne 36 and Kouvaritakis and Cannon 37 and practical inspiration from Rahman and Ikeura 29 and Rahman et al 35 for the PARS, as shown Figure 10. Mean (n ¼ 10) workload rating scores (out of 100) with standard deviations for the six dimensions of the NASA TLX for the FAC with lightweight and heavy object manipulation.…”
Section: Model Predictive Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference [4] describes a genetic algorithm for a collaborative assembly station which minimises the assembly time and costs. In [14], a trust-based dynamic subtask allocation strategy for manufacturing assembly processes has been presented. The method, which relies on a Model Predictive Control (MPC) scheme, accounts for human and robot performance levels, as well as far their bilateral trust dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, by trust of teachers and students in robotics, we mean their willingness to believe in, understand, and accept the solutions provided by robots and to rely on the contributions of robots in STEM teaching and learning. 24 Many factors of robots may affect the trust of teachers and students towards robots. 25 However, two critical factors, viz., the robot's overall performance and its incomprehensible or erroneous response while working with its human counterparts (teachers and students) usually affect a human's trust in the robots.…”
Section: Introductionmentioning
confidence: 99%